Leadership in nursing: professional accountability and responsibility - Bhullar, Anu; Rose, Serena (My University, 2026)
Expectations for new graduate nurses (NGNs) upon entry to practice are extensive. Alberta’s nursing regulatory body, the College of Registered Nurses of Alberta (CRNA), outlines these competencies in several key documents. In this paper, we explore the importance of NGNs, as novice healthcare leaders, to intentionally pursue the foundational standard of accountability and responsibility through effective communication. We will discuss this competency’s presentation, importance, methods of practice, and methods of growth assessment. These insights will be supported by relevant literature and a personal anecdote, providing a well-rounded perspective for the proposed guidance on nursing leadership competencies for NGNs.
Keywords: new graduate nurses (NGN); College of Registered Nurses of Alberta (CRNA); foundational standard of accountability and responsibility